Transcriptional profiling reveals H.pylori-associated genes induced inflammatory cell infiltration and chemoresistance in gastric cancer - Jinshui Tan; Jinshui Tan; Zhengxin Wu; Yuankun Liu; Wei Wang; Wei Wang; Wenjuan Qin; Guangchao Pan; Guangchao Pan; Yubo Xiong; Yubo Xiong; Jingsong Ma; et al. (Frontiers in Immunology)
BackgroundH. pylori infection is closely associated with the tumor microenvironment (TME) in gastric cancer (GC), yet its underlying mechanism is elusive. Hence, it is imperative to explore the microenvironment and drug resistance arising from H. pylori to enhance therapeutic strategies for GC.MethodsEmploying transcriptional bioinformatics, we computed a H. pylori-associated prognostic index (HPI) using datasets from TCGA and GSE62254 containing ACSM5 and HSPB2 gene expression. We assessed IC50 values for anticancer drugs and immune cell infiltration to evaluate the therapeutics and TME based on the HPI. Further, we validated the transcriptional profiling findings by examining drug sensitivity transfected with siACSM5 and siHSPB2 and analyzing scRNA-seq data and clinical patient samples.ResultsACSM5 and HSPB2 were identified as correlates of H. pylori infection in GC. Significantly, we established the H. pylori-associated prognostic index (HPI) and found that a high HPI was linked with a worse prognosis. Classification based on the HPI indicated an enhanced infiltration of tumor microenvironment cells and resistance to anti-tumor drugs.ConclusionThe HPI, reflecting newly identified and complementary biomarkers, correlated with the TME and could accurately project chemoresistance and an altered immune cell distribution in GC patients, thus providing clinical guidance on therapeutic interventions.